Percepción de estudiantes de derecho sobre la desinformación de términos jurídicos en facebook. caso: noticias sobre odebrecht en el medio zona cero (2024)
This thesis aims to explore the perception that law students at the University of La Costa, enrolled in the subject of Legal and Sociolegal Research, have regarding the misinformation present in political news involving legal concepts. The analyzed news items are related to the Latin American corruption case known as 'Odebrecht' and were extracted from the Facebook profile of the Barranquilla-based media outlet 'Zona Cero'. Media monitoring was conducted from January to July 2023, with 960 posts per month (approximately 32 news items per day), out of which nine were about the Odebrecht case, and of these nine, five contained misinformation. Subsequently, a focus group was conducted where students analyzed the accuracy of these news items. The results reveal little credibility in local media among students, affecting their interpretation of news. Additionally, the need to improve critical thinking skills and the handling of legal language among students was emphasized, as they lack specific tools to identify when a news item contains misinformation. It is recommended to conduct additional studies that allow the implementation of educational activities aimed at providing tools to combat misinformation, including subjects in the curriculum that address the evaluation of the truthfulness of information on social networks.